Jonathan Frankel and Ezra Mendelsohn, editors. The Protestant-Jewish Conundrum (Studies in Contemporary Jewry, Vol. XXIV) - Soloff, Emily D. (Studies in Christian-Jewish Relations, 2011)
No abstract is available.